2019
DOI: 10.1177/1046878118823033
|View full text |Cite
|
Sign up to set email alerts
|

Not Only for the (Tom) boys: Gender Variables as Predictors for Playing Motivations, Passion, and Addiction for MMORPGs

Abstract: Background. Research on playing motivation and passion for MMORPGs and gender has so far mainly focused on biological sex and neglected variables related to social gender such as masculinity and femininity. As some playing motivations and obsessive passion are assumed to be related to problematic game play, problematic game play is still considered a male phenomenon, often based on mainly male samples and disregarding underlying causes in problematic tendencies that could explain or extent findings on biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 58 publications
(78 reference statements)
1
25
0
Order By: Relevance
“…Men being more likely than women to work to acquire expensive items might be similarly viewed in terms of men's greater independence and also in terms of their greater motivation to achieve success within MMORPGs (Jansz et al, 2010;Williams et al, 2009;Yee, 2006). By contrast, women being more likely than men to seek in-game awards and achievements seems difficult to reconcile with the sex difference just mentioned (i.e., men more likely to work to acquire expensive items), but it may indicate that the sex difference in achievement motivation in MMORPGs may be less reliable than is sometimes assumed (Kneer et al, 2019). A related possibility is that achievement motivation does not differ in men and women overall, yet the contexts that evoke achievement motivation may differ.…”
Section: Patterns Of Sex Differences In Competitive Behaviorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Men being more likely than women to work to acquire expensive items might be similarly viewed in terms of men's greater independence and also in terms of their greater motivation to achieve success within MMORPGs (Jansz et al, 2010;Williams et al, 2009;Yee, 2006). By contrast, women being more likely than men to seek in-game awards and achievements seems difficult to reconcile with the sex difference just mentioned (i.e., men more likely to work to acquire expensive items), but it may indicate that the sex difference in achievement motivation in MMORPGs may be less reliable than is sometimes assumed (Kneer et al, 2019). A related possibility is that achievement motivation does not differ in men and women overall, yet the contexts that evoke achievement motivation may differ.…”
Section: Patterns Of Sex Differences In Competitive Behaviorsmentioning
confidence: 94%
“…In particular, the MTurk sample will be biased towards individuals who choose to work on that platform, and the Reddit sample will be biased towards those who are active in that particular community. One indication of this bias is that the percentage of women in the Reddit sample (11%) is substantially lower than in other academic studies (20-45%), although these studies mainly use convenience samples and thus may also not be representative of all MMORPG players (Huh & Williams, 2010;Kneer et al, 2019;Lou et al, 2013;Martey et al, 2014;Williams et al, 2009;Yee et al, 2011Yee et al, , 2012. A few counterpoints warrant mentioning, however.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, in some studies, men showed predominantly achievement, control, and manipulation motives, while women indicated social and immersion motives with higher scores in the seeking of relationship, socialization, and escapism (Jansz et al, 2010;Yee, 2006). However, as Kneer et al (2019) showed, these motivations are also predicted by gender-related personality traits.…”
Section: Impact On Gaming Motivations and Enjoymentmentioning
confidence: 99%
“…Likewise, Julia Kneer, Sanne Franken, and Sabine Reich’s (2019) article, “Not only for the (tom)boys: Gender variables as predictors for playing motivations, passion, and addiction for MMORPGs”, contribute to more than one discourse. Issues of gender and gaming, and addiction to gaming, are still under heavy debate, rational as well as highly toxic critique, and repeated media (mis)representation.…”
mentioning
confidence: 99%